2007
DOI: 10.2514/1.26090
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of Nanoscale Al/MoO3 Thermite in Microchannels

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(90 citation statements)
references
References 25 publications
2
88
0
Order By: Relevance
“…[ [4][5][6][7][8][9] These investigations established unambiguously that thermitenanocomposite ignition and combustion properties can be affected by varying the size of the constituents and their intimacy. [4,5,[7][8][9][10][11][12][13][14][15][16] For instance, decreasing the size of the nanoparticles enhances the combustion rate and lowers the ignition temperature.…”
Section: Introductionmentioning
confidence: 84%
“…[ [4][5][6][7][8][9] These investigations established unambiguously that thermitenanocomposite ignition and combustion properties can be affected by varying the size of the constituents and their intimacy. [4,5,[7][8][9][10][11][12][13][14][15][16] For instance, decreasing the size of the nanoparticles enhances the combustion rate and lowers the ignition temperature.…”
Section: Introductionmentioning
confidence: 84%
“…A large amount of heat (Q) is released in the classical reduction reaction [10] 0.65-1. 6 80 200 -30 nm [11] Al-WO 3 1-1.5 80 100 -20 nm [12] Al-Bi 2 O 3 1-1.5 80 25-2 μm (filaments) [13] 1 40, 100 40, 108, 321, 416 mn [12] Al-CuO 1-1.5 80 100-20 mn [12] Al-Fe 2 O 3 0.9-4 52 BET = 50-300 m 2 /g [14] A + y…”
Section: Powder Nanosystemsmentioning
confidence: 99%
“…For this reason, the use of the same initial nanopowders, which were stored and mixed under different conditions, usually yields different results in terms of ignition and combustion characteristics of such systems. The data on the chemical compositions and particle sizes of reagents of some superthermite systems studied in [5][6][7][8][9][10][11][12][13][14] are summarized in Table 1. The widest range of metal nanoparticles was provided in experiments with the Al-MoO 3 system.…”
Section: Powder Nanosystemsmentioning
confidence: 99%
“…Additional information on the research conducted on nanothermites can be found in Refs. [186][187][188][189][190][191][192][193]. …”
Section: Figure 137mentioning
confidence: 99%